2010
DOI: 10.1021/ja9098005
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide N,N-Dimethylaminodiboranates: Highly Volatile Precursors for the Deposition of Lanthanide-Containing Thin Films

Abstract: New lanthanide CVD precursors of stoichiometry Ln(H(3)BNMe(2)BH(3))(3) have been prepared, where Ln = La, Ce, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er, Tm, and Lu. The ligand is N,N-dimethylaminodiboranate, a new kind of multidentate borohydride. The structures of the Ln(H(3)BNMe(2)BH(3))(3) complexes are highly dependent on the size of the lanthanide ions: the coordination number decreases from Pr (CN = 14) to Sm (CN = 13) to Er (CN = 12) corresponding with the decrease in ionic radii. The Ln(H(3)BNMe(2)BH(3))(3) compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 35 publications
4
64
0
Order By: Relevance
“…Some derivatives of these compounds also have high coordination numbers, such as the 14-coordinate tetrahydrofuran complex [U(BH 4 ) 4 (thf) 2 ]. This compound extends our recent studies of a new class of chelating borohydride ligands, that is, the aminodiboranates, [23][24][25][26] some of which form highly volatile complexes that are useful as precursors for the chemical vapor deposition of thin films. [16,22] Herein, we report the synthesis, single-crystal X-ray and neutron diffraction studies, and DFT investigations of the first 15-coordinate complex.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Some derivatives of these compounds also have high coordination numbers, such as the 14-coordinate tetrahydrofuran complex [U(BH 4 ) 4 (thf) 2 ]. This compound extends our recent studies of a new class of chelating borohydride ligands, that is, the aminodiboranates, [23][24][25][26] some of which form highly volatile complexes that are useful as precursors for the chemical vapor deposition of thin films. [16,22] Herein, we report the synthesis, single-crystal X-ray and neutron diffraction studies, and DFT investigations of the first 15-coordinate complex.…”
mentioning
confidence: 58%
“…[21] No complex of any kind, however, has been definitively shown to adopt a Werner coordination number higher than 14. [25,26] Reaction of ThCl 4 with four equivalents of sodium N,Ndimethylaminodiboranate, Na(H 3 BNMe 2 BH 3 ), in tetrahydrofuran produced [Th(H 3 BNMe 2 BH 3 ) 4 ] (1), which could be isolated as colorless prisms by crystallization from diethyl ether. DFT calculations suggest that this complex may adopt a 16-coordinate structure in the gas phase.…”
mentioning
confidence: 99%
“…59 The divalent and trivalent products can be easily distinguished by their colors. The Eu 2þ complex 1 is off-white, whereas its Eu 3þ analogue is yellow; for ytterbium, the colors are reversed: the Yb 2þ complex 2 is intensely yellow, whereas the Yb 3þ analogue is pale-yellow.…”
Section: Resultsmentioning
confidence: 99%
“…[55][56][57][58] We have previously shown that N, N-dimethylaminodiboranate (DMADB) complexes of trivalent lanthanide are highly volatile and useful as chemical vapor deposition and atomic layer deposition precursors to lanthanide-containing thin films. 59 We now describe the synthesis, characterization, and molecular structures of divalent lanthanide N,N-dimethylaminodiboranates. In several of these reactions, the DMADB ligand serves simultaneously as a ligand and as a reductant.…”
Section: Introductionmentioning
confidence: 99%
“…31 Consequently, lanthanide complexes containing DMADB ligands are among the most volatile compounds known for these elements. 32,33 Several M(DMADB) 3 complexes with trivalent lanthanides (all except promethium) and an actinide (uranium) have been reported. 31−33 Because the DMADB ligand can chelate to or bridge between two metal centers, a variety of solid-state structures have been observed depending on the size of the M 3+ ion: the coordination number increases from 12 to 14 as the ionic radius of the metal center becomes larger.…”
Section: ■ Introductionmentioning
confidence: 99%